Antiplatelet Therapy for Atherothrombotic Disease in 2022—From Population to Patient-Centered Approaches - Jourdi, Georges; Godier, Anne; Lordkipanidzé, Marie; Marquis-Gravel, Guillaume; Gaussem, Pascale (Frontiers in Cardiovascular Medicine, 2022)
Antiplatelet agents, with aspirin (ASA) and P2Y12 receptor antagonists as major key molecules, are currently the cornerstone of pharmacological treatment of atherothrombotic events including a variety of cardio- and cerebro-vascular as well as peripheral artery diseases. Over the last decades, significant changes have been made to antiplatelet therapeutic and prophylactic strategies. The shift from a population-based approach to patient-centered precision medicine requires greater awareness of individual risks and benefits associated with the different antiplatelet strategies, so that the right patient gets the right therapy at the right time. In this review, we present the currently available antiplatelet agents, outline different management strategies, particularly in case of bleeding or in perioperative setting, and develop the concept of high on-treatment platelet reactivity and the steps towards person-centered precision medicine aiming to optimize patient care.